Pelatihan penampungan dan pengolahan semen kambing untuk meningkatkan pengetahuan dan keterampilan peternak: Collection and processing of goat semen to enhance livestock productivity - Mansur, Musdalifa; Wahyuni, Sri; Mutiara, Mutiara (Fakultas Peternakan Universitas Papua, 2024)
ABSTRACT Suboptimal reproduction issues often hamper the productivity of goat farming in Indonesia. One potential solution to improve productivity is through artificial insemination (AI) technology using high-quality goat semen. However, the knowledge and skills of farmers in collecting and processing goat semen are still limited. This community service program aims to increase the productivity of goat farming through education and training on the techniques of semen collection and processing, as well as the implementation of artificial insemination for local farmers. The methods used include socialization and education through seminars and workshops and technical training in semen collection, processing, storage, and artificial insemination techniques. Additionally, periodic assistance and monitoring are conducted to evaluate program's success. The results of this program show an increase in farmers' knowledge and skills in semen collection, processing, and use of goat semen. This is reflected in the reduction of semen damage rates, improvement in the quality of produced semen, and an increase in goat birth rates through artificial insemination. Additionally, there is an improvement in the genetic quality and productivity of goats in the targeted area. This program is expected to have a significant positive impact on the productivity of goat farming. It can be adopted and implemented in other areas facing similar issues, thereby providing broader benefits in the development of goat farming in Indonesia. Keywords: Artificial insemination; Farming productivity; Goats; Semen collection; Semen processing ABSTRAK Produktivitas peternakan kambing di Indonesia seringkali terhambat oleh masalah reproduksi yang kurang optimal. Salah satu solusi potensial untuk meningkatkan produktivitas adalah dengan teknologi inseminasi buatan (IB) menggunakan semen kambing berkualitas tinggi. Namun, pengetahuan dan keterampilan peternak dalam penampungan dan pengolahan semen kambing masih terbatas. Program pengabdian masyarakat ini bertujuan untuk meningkatkan produktivitas peternakan kambing melalui edukasi dan pelatihan tentang teknik penampungan dan pengolahan semen kambing serta pelaksanaan inseminasi buatan kepada peternak lokal. Metode yang digunakan meliputi sosialisasi dan edukasi melalui seminar dan lokakarya, pelatihan teknis penampungan, pengolahan, penyimpanan semen, serta teknik inseminasi buatan. Selain itu, dilakukan pendampingan dan monitoring secara berkala untuk mengevaluasi keberhasilan program. Hasil dari program ini menunjukkan adanya peningkatan pengetahuan dan keterampilan peternak dalam teknik penampungan, pengolahan, dan penggunaan semen kambing. Hal ini tercermin dari penurunan angka kerusakan semen, peningkatan kualitas semen yang dihasilkan, dan peningkatan angka kelahiran kambing melalui inseminasi buatan. Selain itu, terdapat peningkatan kualitas genetik dan produktivitas kambing di wilayah sasaran. Program ini diharapkan dapat memberikan dampak positif yang signifikan terhadap produktivitas peternakan kambing dan dapat diadopsi serta diterapkan di daerah lain yang memiliki permasalahan serupa, sehingga memberikan manfaat yang lebih luas dalam pengembangan peternakan kambing di Indonesia. Kata kunci: Inseminasi buatan; Kambing; Penampungan semen; Pengolahan semen; Produktivitas peternakan